An anti-symmetric dual (ASD) Z-scheme photocatalytic system: (ZnIn2S4/Er3+:Y3Al5O12@ZnTiO3/CaIn2S4) for organic pollutants degradation with simultaneous hydrogen evolution. (8th March 2019) - Wang, Jing; Wang, Di; Zhang, Xu; Zhao, Cheng; Zhang, Meng; Zhang, Zhaohong; Wang, Jun
Abstract: An anti-symmetric dual (ASD) Z-scheme ZnIn2 S4 /Er 3+ :Y3 Al5 O12 @ZnTiO3 /CaIn2 S4 photocatalyst was prepared by isoelectric point and calcination methods. The photocatalytic activity is estimated via degradation of Acid Orange II as a target organic contaminant with simultaneous hydrogen evolution under simulated solar-light irradiation. The prepared ASD Z-scheme ZnIn2 S4 /Er 3+ :Y3 Al5 O12 @ZnTiO3 /CaIn2 S4 photocatalyst has a high photocatalytic activity, which can be assigned to the enlarged photoresponse range, increased reduction surface and enhanced separation efficiency of photo-induced carriers. Furthermore, the cyclic experiment proves that the prepared ASD Z-scheme ZnIn2 S4 /Er 3+ :Y3 Al5 O12 @ZnTiO3 /CaIn2 S4 photocatalyst still maintains a high photocatalytic activity within five repetitive cycles. Moreover, the mechanism on photocatalytic degradation of organic pollutants with simultaneous hydrogen evolution caused by ASD Z-scheme ZnIn2 S4 /Er 3+ :Y3 Al5 O12 @ZnTiO3 /CaIn2 S4 photocatalyst is proposed. It is wished that this study could provide a promising pathway for effective degradation and rapid hydrogen production. Highlights: A novel ASD Z-scheme ZnIn2 S4 /Er 3+ :Y3 Al5 O12 @ZnTiO3 /CaIn2 S4 composite is designed. Er 3+ :Y3 Al5 O12 converts low energy light into high energy light to activate ZnTiO3 . ASD Z-scheme can perform simultaneous pollutant degradation and hydrogen evolution. ASD Z-scheme gives two more negative potential conduction bands producing hydrogen. ZnIn2 S4 /Er 3+ :Y3 Al5 O12 @ZnTiO3 /CaIn2 S4 plays a good Z-scheme charge transfer process.